1996
DOI: 10.5144/0256-4947.1996.53
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma: A Review of 140 Cases

Abstract: Saudi Arabia appears to have an unusually high incidence of hepatocellular carcinoma, which has been causally associated with a high prevalence of hepatitis B virus (HBV). Other risk factors, including hepatitis C virus (HCV) infection are currently not known. A study was undertaken to establish the risk factors and clinicopathological features of hepatocellular carcinoma in Saudi Arabia. The profiles of 140 patients with a biopsy-proven hepatocellular carcinoma were analyzed. Demographic data revealed a stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…This result is similar to the recent findings of Al Sohaibani et al in 2011 and Al Sawat et al in 2013 [9] [20]. However, this differs from previously reported HCC data in Saudi Arabia from 1990 to 2004, which showed that HBV-associated liver disease was the predominant cause of HCC in KSA [19] [21] [22]. This recent drop in CHB as a cause for HCC and liver disease is related to the implementation of the HBV vaccination neonatal program in the country approximately 25 years ago [7] [8].…”
Section: Discussionsupporting
confidence: 90%
“…This result is similar to the recent findings of Al Sohaibani et al in 2011 and Al Sawat et al in 2013 [9] [20]. However, this differs from previously reported HCC data in Saudi Arabia from 1990 to 2004, which showed that HBV-associated liver disease was the predominant cause of HCC in KSA [19] [21] [22]. This recent drop in CHB as a cause for HCC and liver disease is related to the implementation of the HBV vaccination neonatal program in the country approximately 25 years ago [7] [8].…”
Section: Discussionsupporting
confidence: 90%
“…HCV infection (149,150). Considerably higher alcohol use is found in other countries, especially among PWID and prisoners.…”
Section: Recommendations On Care Of People Infected With Hcvmentioning
confidence: 99%
“…It is mostly seen in men (male/female ratio 2.4:1) and generally occurs in the elderly ages (1). But in high incidence areas, male/female ratio can increase up to 5.7:1 and the disease can affect people in their thirties (3,4). HCC still has a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%